Instrumentos jurídicos del proceso de paz - Carlos Parra Dussan; Carolina Herrera Nossa (Revista de Derecho)
This article makes a review of the legislation in force in Colombia on peace processes that we have had, recommending to the Colombian State, take into account the main settings for the current negotiation, from the perspective of the right to peace embodied in our Constitution and the legal framework for the peace established in the Legislative Act 1 of 2012.